2017
DOI: 10.1177/1078155217690922
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of malignancy-associated venous thromboembolism among patients treated with rivaroxaban compared to enoxaparin

Abstract: Purpose Although low-molecular-weight heparin (LMWH) remains the standard of care, factor Xa inhibitors such as rivaroxaban may serve as an alternative treatment for venous thromboembolism (VTE) in patients with active malignancy. The purpose of the analysis was to evaluate outcomes of VTE management in cancer patients treated with rivaroxaban compared to enoxaparin. Methods This single-center retrospective analysis was conducted on patients with malignancy-associated VTE initiated on treatment with either riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…The risk of recurrent VTE ranged from 0% to 13.2% with the most extreme estimates observed in studies including very few patients or not accounting competing risk of death leading to overestimation of event rates; in the majority of studies recurrence risk was approximately 3%‐5%. The risk of major bleeding ranged from 0% to 17%, again with the most extreme estimates obtained in studies with very few patients, for example the estimate of a 17% risk of major bleeding originated from studies with 18 and 48 patients, respectively . Six studies provided estimates of clinically relevant nonmajor bleeding, which ranged from 1.2% to 12.2% (5 events) (Table ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The risk of recurrent VTE ranged from 0% to 13.2% with the most extreme estimates observed in studies including very few patients or not accounting competing risk of death leading to overestimation of event rates; in the majority of studies recurrence risk was approximately 3%‐5%. The risk of major bleeding ranged from 0% to 17%, again with the most extreme estimates obtained in studies with very few patients, for example the estimate of a 17% risk of major bleeding originated from studies with 18 and 48 patients, respectively . Six studies provided estimates of clinically relevant nonmajor bleeding, which ranged from 1.2% to 12.2% (5 events) (Table ; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Rivaroxaban was found to be roughly inferior to enoxaparin in the study. In another study conducted by alexander et al, primary outcome occurred in 7.7% patients in the dabigatran group and 8.8% patients in the enoxaparin group with an absolute risk difference of 1.1% (95% CI, -3.8% to 1.6%) [22] . Furthermore, meta-analysis by Gomez-Outes et al, reported risk of symptomatic VTE with dabigatran (relative risk 0.71, CI 0.23 to 2.12) is similar and comparable to enoxaparin [23] .…”
Section: Discussionmentioning
confidence: 90%
“…According to our predefined criteria, a total of 4 articles and 667 patients were included in the final analysis [ 8 , 9 , 11 , 12 ] (Flow Diagram). The majority of included articles (3 out of 4) were published in 2017.…”
Section: Resultsmentioning
confidence: 99%